2011
DOI: 10.1002/apj.655
|View full text |Cite
|
Sign up to set email alerts
|

Platinum nanoparticles generated in spherical polyelectrolyte brushes and their high catalytic activity

Abstract: Nano‐sized cationic spherical polyelectrolyte brushes (SPBs) consisting of a solid core of polystyrene and a shell of poly(aminoethyl methacrylate hydrochloride) grafted densely on the core were prepared by photo‐emulsion polymerization. They were found to be ideal nanoreactors to generate platinum (Pt) nanoparticles. Because of Donnan equilibrium, SPBs can concentrate and confine the divalent PtCl62− ions as counterions within the brush layer. The PtCl62− ions were reduced into Pt particles with an average si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[88][89][90] Some time ago we demonstrated that spherical polyelectrolyte brushes (SPB) 29,30 are highly suitable carrier system for the immobilization of various metal nanoparticles. 13,14,38,[91][92][93][94][95][96] The SPB particles consist of a polystyrene core onto which a dense layer of polyelectrolyte brushes is grafted. The metal ions are immobilized in the brush layer as counter-ions.…”
Section: Carriers and Nanoreactors: A Surveymentioning
confidence: 99%
“…[88][89][90] Some time ago we demonstrated that spherical polyelectrolyte brushes (SPB) 29,30 are highly suitable carrier system for the immobilization of various metal nanoparticles. 13,14,38,[91][92][93][94][95][96] The SPB particles consist of a polystyrene core onto which a dense layer of polyelectrolyte brushes is grafted. The metal ions are immobilized in the brush layer as counter-ions.…”
Section: Carriers and Nanoreactors: A Surveymentioning
confidence: 99%
“…Among multiple techniques, phase separation by polyelectrolytes was reported to be able to achieve selective protein adsorption. When a polyelectrolyte is modified on a core, a spherical polyelectrolyte brush is formed, which could be an ideal carrier for selective protein adsorption as a mobile stationary phase in a solution. This is different from ion-exchange chromatography by which high resolution of proteins can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The reason was that the reducibility of NaBH 4 was quite strong and it could directly turn TeO 3 2− into Te 2− while N 2 H 4 only could reduce TeO 3 2− to Te under the same condition [15]. And if firstly adding N 2 H 4 , the rapid nucleation of QDs, a crucial factor of highly luminescent QD generation, could be seriously prevented due to the decreasing reaction rate of NaBH 4 at high pH values [16,17]. Because the N 2 H 4 , the strong base, would increase the pH of solution to 13 at which the reaction rate of the next addition of NaBH 4 could slow down and the PL of QDs largely decreased [18].…”
Section: Resultsmentioning
confidence: 99%